Esophageal Abnormalities - Chai, Jianyuan (IntechOpen, 2017)
Human life relies on two basic supplies, oxygen and food. Oxygen can be utilized directly, but food has to go through a long process of digestion to become usable nutrients. The esophagus is the beginning part of this long journey. Because of its critical location, any abnormalities in this part of the body can be devastating and life-threatening and difficult to treat. This book covers many aspects of esophageal disorders, from congenital diseases to cancer. It includes 11 chapters written by highly experienced scholars from all over the world. It is our intention to provide readers an update in esophageal study and to raise the awareness how important this organ to our entire body system.